2018
DOI: 10.1186/s12889-018-5760-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health knowledge among college students in Kenya

Abstract: BackgroundReproductive health knowledge is vital in the growth and development of young people and this impact greatly on their educational and personal outcome as they proceed to adulthood. There has been an increasing occurrence of sexually transmitted infections in institutions of higher learning. The study sought out the strategies used by university students to prevent unplanned pregnancy and determined their knowledge of contraception methods and sexually transmitted infections in Mount Kenya University,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(20 reference statements)
3
4
0
1
Order By: Relevance
“…This finding was consistent with the 2016 UDHS findings which showed that almost 99% of assessed youths knew about modern methods of contraceptives and condoms were the most known modern contraceptive [20]. Similar findings were also found among Kenyan youths [32].…”
Section: Discussionsupporting
confidence: 90%
“…This finding was consistent with the 2016 UDHS findings which showed that almost 99% of assessed youths knew about modern methods of contraceptives and condoms were the most known modern contraceptive [20]. Similar findings were also found among Kenyan youths [32].…”
Section: Discussionsupporting
confidence: 90%
“…Respondents' were knowledgeable about contraceptives, especially with regards to condoms (100%) and oral contraceptives (97.6%). The finding is in line with other studies in KwaZulu-Natal (South Africa), Kenya and Tanzania were research participants were knowledgeable about contraceptives [46][47][48]. Respondents were also knowledgeable about the symptoms of STIs.…”
Section: Knowledge Of Contraceptives and Symptoms Of Stissupporting
confidence: 90%
“…87-93 Retno Heru Setyorini et.al (Husband's support on the use of intrauterine device (IUD) and…) study did not show the effect of knowledge on the use of an IUD or implant. This is in line with a research conducted in different context which showed that contraceptive knowledge possessed by students does not increase its use (Mbugua and Karonjo 2018). The use of IUDs and Implant contraception is influenced by knowledge, social norms (Dynes, Stephenson, Rubardt, & Bartel, 2012), the role of the counselor (Robby et al, 2019), and service limitations (Babalola, Figueroa, and Krenn 2017).…”
Section: Discussionsupporting
confidence: 72%